Magnetic Train Training to Increase Teacher Creativity at Manahan Christian Elementary School, Solo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Educational teaching aids are one of the media that have been prepared during the teaching and learning process at school. Props that have been created to help students understand lesson material more effectively and interestingly. Community service activities have been carried out at the Manahan Christian Elementary School in Solo, Central Java. The activity will be held on June 28 2024. Participants in the Community Service program were attended by elementary school teachers from 4 schools with a total of 68 participants. The implementation of this community service has been divided into two sessions, namely a material presentation session and a teaching aids workshop session. The magnetic train teaching aids workshop at Manahan Christian Elementary School was successfully implemented with a very good response from the participants. Workshop participants have assessed a high level of satisfaction with all aspects of the training, starting from the material that has been delivered (85.7%), the performance of resource persons and facilitators who have provided services (86.5%), to the overall activity sessions carried out (87. 4%) with the satisfaction score obtained reaching the very good category, this workshop succeeded in providing practical knowledge and skills that are relevant to teaching needs in elementary schools.